2017
DOI: 10.1097/prs.0000000000003711
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Safety Data for More than 55,000 Subjects following Breast Implantation: Comparison of Rare Adverse Event Rates with Silicone Implants versus National Norms and Saline Implants

Abstract: Therapeutic, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…There are conflicting data regarding the association of silicone and increased rates of connective tissue disease or other adverse events. Singh et al 12 reviewed 55,000 patients following breast augmentation for up to 8 years and reported no increased risk of systemic disease or adverse events when compared with that reported in national norms or with those with saline implants. However, in 2019, Coroneos et al 13 reviewed nearly 100,000 patients and found an increased incident ratio for Sjogren’s disease, scleroderma, and rheumatoid arthritis in those with silicone implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are conflicting data regarding the association of silicone and increased rates of connective tissue disease or other adverse events. Singh et al 12 reviewed 55,000 patients following breast augmentation for up to 8 years and reported no increased risk of systemic disease or adverse events when compared with that reported in national norms or with those with saline implants. However, in 2019, Coroneos et al 13 reviewed nearly 100,000 patients and found an increased incident ratio for Sjogren’s disease, scleroderma, and rheumatoid arthritis in those with silicone implants.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one study even suggested that left-sided implants seem to be damaged more often owing to surgeons’ overall right handedness. 12 To ensure safety of the implant, surgeons should consider a few guidelines during fat transfer. One should ensure subcutaneous visibility of the tip of the cannula while it is being inserted and avoid plunging the cannula deep.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion and exclusion criteria for BIFS-001 have been published previously. 12,13 This subanalysis of BIFS-001 included only women who experienced live births after undergoing primary augmentation surgery with unilateral or bilateral silicone implants or saline implants. Eligible patients were women aged 22 years or older who were fluent in English or Spanish.…”
Section: Methodsmentioning
confidence: 99%
“…Patients completed questionnaires at baseline and annually after surgery, which included a series of questions regarding pregnancy and lactation as well as other outcomes (eg, adverse events and satisfaction) that are reported separately. 12,14 Mothers who had stopped breast-feeding a baby that was born after their primary augmentation procedure were asked if they had any of the following complications before they stopped breast-feeding: mastitis, not enough milk production, too much milk production, excess pain, nipple inversion, or another problem with their breasts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation